Toward a Circular Bioeconomy: Exploring Pineapple Stem Starch Film as a Plastic Substitute in Single Use Applications - Atitiya Namphonsane; Phattarakarn Suwannachat; Chin Hua Chia; Rungtiwa Wongsagonsup; Siwaporn Meejoo Smith; Taweechai Amornsakchai (Membranes, 2023)
In this study, biodegradable starch film was developed from pineapple stem waste as a substitute for non-biodegradable petroleum-based films for single-use applications where strength is not too demanding. High amylose starch from a pineapple stem was used as the matrix. Glycerol and citric acid were used as additives to adjust the ductility of the material. Glycerol content was fixed at 25% while that of citric acid varied from 0 to 15% by weight of starch. Films with a wide range of mechanical properties can be prepared. As more citric acid is added, the film becomes softer and weaker, and has greater elongation at the break. Properties range from a strength of about 21.5 MPa and 2.9% elongation to a strength of about 6.8 MPa and 35.7% elongation. An X-ray diffraction study showed that the films were semi-crystalline. The films were also found to be water-resistant and can be heat-sealed. An example of a single-use package was demonstrated. A soil burial test confirmed that the material was biodegradable and completely disintegrated into sizes smaller than 1 mm within one month.